Perlindungan Hukum Terhadap Korban Tindak Pidana Kdrt Di Indonesia Dan India - Rina Shahriyani Shahrullah; Merlinda Merlinda (Fakultas Hukum, Universitas Internasional Batam, 2014)
Domestic violence is a criminal act where there is abuse of power or authority of a man against the woman who not only causes physical injuries, but also mentally and psychologically. The purpose of this study was to describe how domestic violence that occurred in Indonesia and India with sticking in the implementation of the CEDAW.This research uses normative research and then comparative method. Secondary data is collected using the library research. As all datas are collected, those datas are then being processed and analyzed qualitatively which means to group data and compile systematically. Further conclusions drawn related to this study, then decribed descriptively.Based on this research, it obtained information that the ratification of CEDAW both in Indonesia and India, the two countries have good aim to make the handling and protection of all victims of domestic violence in their respective countries. But in this study, it was found that the treatment and legal protection of victims of domestic violence in Indonesia is better than India. Therefore, the study recommends that treatment and legal protection of victims of domestic violence India should adopt the strength of handling and legal protection of victims of domestic violence in Indonesia.